Determinants of learning and development initiatives - Saidi, Mas Idayu (2011)
This study attempts to address issues regarding relationship between organizational (government policies, line management involvement, top management support, outsourcing and external consultant) and individual (motivation to learn, learning skills and peer support) factors of learning and development (L&D) towards effective implementation of L&D and their influences on the effectiveness of L&D initiatives implementation. This research adopts a quantitative approach based on 103 employees in selected ABC Bank branches in Johor Bahru. Four-section of self-administered survey questionnaire was constructed with 60 items related to L&D factors and effective implementation of L&D initiatives. Frequency and descriptive test, Pearson correlation and multivariate analysis are being applied. The findings indicated three organizational factors (top management support, outsourcing, and external consultants) and two individual factors (learning skills and peer support) correlated significantly with effective implementation of L&D initiatives. However, the other two organizational (government policies and line managers? involvement) and one individual factor (motivation to learn) are found to have no relationship at all. The findings from multivariate analysis using multiple linear regression analysis indicated that peer support (ß = 0.591) is the strongest factor influencing effective implementation of L&D initiatives. However, the other two factors (learning skill and outsourcing) were also found to influence the dependent variable, although limited. The findings are hoped to provide evidences regarding type and responsibility to L&D initiatives, and to increase understanding of the L&D factors influencing effective implementation of L&D in ABC Bank, Johor Bahru.